Measuring the success of massive open online courses: a mixed-method case study - Elsayed Mohamed, Umniya Usama; Salleh, Norsaremah (IEEE, 2021)
Massive Open Online Courses (MOOCs) have recently experienced rapid development and garnered significant attention from various populations. They have drastically changed the way we learn as well as how we teach. The main aim of MOOCs is to provide new opportunities to a massive number of learners to attend online courses from anywhere all over the world. MOOC enrolment rates can be astoundingly high; still, their completion rates are frequently disappointingly low. Nevertheless, as courses, the participants’ enrolment and learning within the MOOCs must be considered when assessing their success. The main purpose of this research is to identify what makes MOOCs successful in its implementation. This research also aims to identify how the current MOOCs offered in higher education institutes are catering to the different learning styles of student and to evaluate the effectiveness of MOOC for teaching and learning.